On Generalized Sasakian-Space-Forms. (27th December 2012) - Nagaraja, H. G.; Somashekhara, G.; Shashidhar, Savithri
Abstract : The purpose of the present paper is to characterize pseudoprojectively flat and pseudoprojective semisymmetric generalized Sasakian-space-forms.